Meretas Jalan Pendidikan Islam Modern melalui Perspektif Neurosains - Apris; Lahmi, Ahmad; Dasrizal Dahlan; Rosniati Hakim; Ari Prima (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
This article aims to explore the integration between neuroscience and Islamic education in order to formulate a model of modern Islamic education that is more effective, scientific, and deeply rooted in spiritual values. This study employs a qualitative method with a library research approach, involving the examination of primary sources such as classical works of al-Ghazali and Ibn Sina, along with verses from the Qur’an and Hadith, which are analyzed alongside contemporary theories of neuroscience. Content analysis is used to identify key concepts, relevant neuroscientific principles applicable to learning processes, and to build an integrative foundation that bridges the two disciplines. A hermeneutic approach is also applied to interpret Islamic texts contextually. The findings indicate that this integration opens significant opportunities for developing a holistic and sustainable educational system. Core principles of neuroscience—such as neuroplasticity, emotional engagement in learning, multisensory instruction, and individualized learning—are highly relevant to Islamic educational concepts such as fitrah, ta’dib, tazkiyah, and tarbiyah. The intersection between these perspectives provides a robust conceptual foundation for curriculum development and learning strategies that are not only rational and empirical but also transcendental. Thus, this article offers a new framework for Islamic education aimed at nurturing intellectually excellent, spiritually mature, and socially adaptive generations.